Differentiated Learning: The Role of Gallery Walk and Students’ 21st Century Competence - Suparno, Suparno; Marulina, Dya; Saptono, Ari; Wibowo, Agus; Narmaditya, Bagus Shandy (Dinamika Pendidikan, 2023)
This research aims to improve students' 21st-century competencies. Differentiated learning with the gallery walk method is expected to provide learning competencies evenly and fairly. The development of Bruce Joyce's learning model, which actualizes individual abilities and differences, is the basis for the study of learning differentiation development in this study. Quasi-experimental quantitative research involves a control class with normal learning and an experimental class with the application of the gallery walk method and differentiated learning. Participants of this study consist of 60 students at Avicenna Jagakarsa High School - South Jakarta, Indonesia. A differentiated learning model using the Gallery walk method was conducted in two classes, then measured its effectiveness. The results of this study found that all students were able to take initiative, be active and build new knowledge and experiences, increase collaboration in learning groups, think openly and accept other people’s thoughts, and foster leadership. In the material aspect, students can analyze learning questions contextually and challenge them according to 21st-century learning competencies. For future researchers to be able to research learning differentiation in other learning materials as well as in different competencies.